2021
DOI: 10.1177/10963480211069173
|View full text |Cite
|
Sign up to set email alerts
|

What is a Theme Park? A Synthesis and Research Framework

Abstract: Theme parks have attracted extensive scholarly attention within and outside the tourism literature. These parks have been studied from various stances, yet a uniform definition and integrated framework remain lacking for theme park research and practice. Based on a comprehensive review and research synthesis, this article defines a theme park as a dedicated space featuring five main characteristics: thematic identity, closed space with controlled access, hybrid consumption, performative labor, and merchandisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 129 publications
(249 reference statements)
0
12
0
1
Order By: Relevance
“…The study context is Chinese-operated parks in China, excluding global brands such as Disney, due to the consideration that Disney’s stories are different in style and structure from those in most domestic theme parks in China, making it hard to determine which elements matter. This research is a contribution to the shaping of interdisciplinary theme park tourism research as suggested by Liang and Li (2021). The results foster the theoretical progress on immersion in the theme park context and inform the industry on how to design and deliver immersive and meaningful experiences within this market.…”
Section: Introductionmentioning
confidence: 53%
“…The study context is Chinese-operated parks in China, excluding global brands such as Disney, due to the consideration that Disney’s stories are different in style and structure from those in most domestic theme parks in China, making it hard to determine which elements matter. This research is a contribution to the shaping of interdisciplinary theme park tourism research as suggested by Liang and Li (2021). The results foster the theoretical progress on immersion in the theme park context and inform the industry on how to design and deliver immersive and meaningful experiences within this market.…”
Section: Introductionmentioning
confidence: 53%
“…Disneyleşme kavramı da, Ritzer (2019) (Bryman, 1999;Langhof ve Güldenberg, 2019;Liang ve Li, 2021). Temalaştırma, Disney parklarının en belirgin etkisini belirtmekte, herhangi bir sunumun fiziksel ortam da dahil olmak üzere tüm bileşenlerinin belirlenen bir tema etrafında tasarlanmasını ifade etmektedir.…”
Section: Disneyleşmeunclassified
“…Heritage park refers to heritage attractions with a unified theme for preserving and interpreting some aspects of national culture (e.g., Timbertown, Australia) [8]. Comparing these two different types of theme parks, the former (amusement park) features various rides and games to entertain visitors and apply different themes to its rides, games, and other attractions [14]. At the same time, visitors can become part of the story through the fantasy created by creative landscapes, architecture, characters, food and other elements as they experience the entertainment nature of the theme park.…”
Section: Theme Parks In Tourismmentioning
confidence: 99%
“…Previous studies involving destination image research have mainly focused on heritage as well as cultural tourism destinations [7]. With the continuous impact of COVID-19 on tourism, the theme park experience has gradually become an important destination choice for tourists during the COVID-19 pandemic [14], considering that theme park destinations are diverse in experience types because of their efficiency. However, when reviewing previous studies, most of the studies involving theme park destinations have mostly focused on the pre-COVID-19 period [10].…”
Section: Theoretical Contributionsmentioning
confidence: 99%
See 1 more Smart Citation